2016
DOI: 10.1136/bmjspcare-2015-001035
|View full text |Cite
|
Sign up to set email alerts
|

Palliative chemotherapy among people living in poverty with metastasised colon cancer: facilitation by primary care and health insurance

Abstract: Background Many Americans with metastasised colon cancer do not receive indicated palliative chemotherapy. We examined the effects of health insurance and physician supplies on such chemotherapy in California. Methods We analysed registry data for 1199 people with metastasised colon cancer diagnosed between 1996 and 2000 and followed for 1 year. We obtained data on health insurance, census tract-based socioeconomic status and county-level physician supplies. Poor neighbourhoods were oversampled and the crite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
1
2
0
Order By: Relevance
“…A study by Cunningham et al 10 also showed that patients receiving PC for incurable esophagogastric cancer were more likely to be male (> 80%) and younger (median age, 62-65 years). Lack of receipt of PC because of lower socioeconomic status has been reported for metastatic colon cancer in the United States 22,23 and for non–small-cell lung cancer in Canada, 24 and this finding is supported by our study in that those in the lowest quintile were less likely to receive PC. Although Canada has a single-payer health insurance system, socioeconomically disadvantaged individuals may still not receive recommended care secondary to other related barriers such as travel costs, with out-of-pocket expenses, which may be prohibitive.…”
Section: Discussionsupporting
confidence: 87%
“…A study by Cunningham et al 10 also showed that patients receiving PC for incurable esophagogastric cancer were more likely to be male (> 80%) and younger (median age, 62-65 years). Lack of receipt of PC because of lower socioeconomic status has been reported for metastatic colon cancer in the United States 22,23 and for non–small-cell lung cancer in Canada, 24 and this finding is supported by our study in that those in the lowest quintile were less likely to receive PC. Although Canada has a single-payer health insurance system, socioeconomically disadvantaged individuals may still not receive recommended care secondary to other related barriers such as travel costs, with out-of-pocket expenses, which may be prohibitive.…”
Section: Discussionsupporting
confidence: 87%
“…While prior literature has identified fear of discrimination and similar barriers based on sexual orientation or gender identity as reasons for a lack of communication, 14,49 these reasons were not overt in this study. Participants rarely attributed negative experiences to discrimination or mistrust directly, although reflections they shared did reveal behavior that structurally may have impacted the communication between patients and clinicians.…”
Section: Discussionmentioning
confidence: 82%
“…Like other structural barriers such as poverty and insurance inadequacy, barriers based on sexual orientation and identity loom largest when one is most in need of care and comfort, especially during the EOL period (Gorey et al, 2016). In the face of these realities it is imperative for LGBT people to communicate and document their EOL preferences.…”
mentioning
confidence: 99%